Apperception of Sufism: sociocultural background (evidence from the Crimean ulus of the golden horde) - Chernysheva, Elena V. (Linguistics and Culture Review, 2021)
The study states that the spread of Sufi teachings in Crimea in the 13th-15th centuries should be considered as a display of the continuous recursiveness of spiritual culture. The prerequisites for apperception are developing as a result of the formation of an institutional matrix, the basis of which was the union of the so-called nomadic empires and Hellenistic states. Maintenance of the Khazar heritage, the impact of the Hellenistic culture, and recursive practice contributed to the spread of Sufism. The atmosphere of the Golden Horde became a certain “fertiliser” for the establishment of the social structure and development of the spiritual life of the medieval Turkic world. The research highlights the specifics of Jochid rulers’ attitude towards Christians. The study describes the role of the first Muslim rulers in the development of new religious traditions of the state, the spread of the Arab-Muslim educational model in the Crimean ulus, the impact of Sufi brotherhoods on the socio-cultural development of Crimea and the influence of prominent Sufis on the ruling elite. In conclusion, the apperception of Sufism is an organic, tradition-based perception of doctrine as the basis of the medieval Crimea’s ideology.